Hubungan Antara Gaya Belajar Dengan Prestasi Belajar IPA Kelas IV SDN 08 Pagi Jakarta Timur - A Awiria; Rossyta Quarisruri (Universitas Sarjanawiyata Tamansiswa, 2019)
The main problem examined in this study is the relationship between learning styles and science learning achievement in class IV SDN 08 East Jakarta. This study aims to obtain knowledge based on data or facts that are valid, true and trusted about the relationship between learning styles and science learning achievement. The hypothesis tested is that there is a relationship between learning styles and science learning achievement in class IV SDN 08 East Jakarta. In accordance with the problem and research objectives, the method used is the survey method with descriptive correlational techniques. The subjects in this study were fourth grade students of SDN 08 Elementary School, East Jakarta, with a population of 101 people and a sample of 34 people with a purposive sampling technique. The instrument used to obtain the variable X data is a questionnaire, while the variable Y data is the report card value. The data analysis technique uses the product moment correlation method to test the research hypothesis with Î± = 5%, the result of rxy (r count) is 0.47 with r table (32.5%) is 0.34. Because rxy> r table, it can be concluded that there is a relationship between learning styles and science learning achievement in class IV SDN 08 East Jakarta.